Severe Hyponatremia-Induced Stress Cardiomyopathy: A Case Report and Review of Literature - Irushna Perera; Sanjeewa Rajapakse; Shamila T. De Silva (Case Reports in Cardiology)
Takotsubo or stress cardiomyopathy is a non ischemic disease affecting the myocardium, which presents with typical features of myocardial ischemia. Although the presentation with acute central chest pain and shortness of breath mimics acute myocardial ischemia, there is an absence of actual disruption of cardiac blood supply via the coronaries due to acute plaque rupture or vascular spasm. The underlying pathophysiology of this clinical entity remains largely unclear, but a definite association with physical or emotional stress has been well established, hence the term “stress cardiomyopathy.” The list of potential triggers continues to grow as the disorder is increasingly detected by clinicians and cardiologists, with better clinical insight and improved availability of cardiac investigations. We report a patient with Takotsubo cardiomyopathy associated with severe hyponatremia.